2007
DOI: 10.1016/j.chembiol.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Emetine Regulates the Alternative Splicing of Bcl-x through a Protein Phosphatase 1-Dependent Mechanism

Abstract: Exon 2 of the Bcl-x gene undergoes alternative splicing in which the Bcl-xS splice variant promotes apoptosis in contrast to the anti-apoptotic splice variant Bcl-xL. In this study, the regulation of the alternative splicing of pre-mRNA of Bcl-x was examined in response to emetine. Treatment of different types of cancer cells with emetine dihydrochloride downregulated the level of Bcl-xL mRNA with a concomitant increase in the mRNA level of Bcl-xS in a dose- and time-dependent manner. Pretreatment with calycul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 37 publications
3
39
0
1
Order By: Relevance
“…S-Adenosylmethionine as well as its metabolites is proapoptotic by stimulating the PP1-catalyzed dephosphorylation of RS proteins, resulting in the formation of the alternative variant Bcl-x S (28). Emetine, an inhibitor of protein synthesis, can also regulate the alternative splicing of Bcl-x transcript to produce proapoptotic Bcl-x S through a PP1-dependent mechanism (29). Based on our results and these previous studies, we speculate that PP1 may play a key role in modulating the pre-mRNA alternative splicing and that any molecule capable of activating PP1 might have the ability to regulate the alternative splicing of apoptotic gene transcripts.…”
Section: Discussionsupporting
confidence: 76%
“…S-Adenosylmethionine as well as its metabolites is proapoptotic by stimulating the PP1-catalyzed dephosphorylation of RS proteins, resulting in the formation of the alternative variant Bcl-x S (28). Emetine, an inhibitor of protein synthesis, can also regulate the alternative splicing of Bcl-x transcript to produce proapoptotic Bcl-x S through a PP1-dependent mechanism (29). Based on our results and these previous studies, we speculate that PP1 may play a key role in modulating the pre-mRNA alternative splicing and that any molecule capable of activating PP1 might have the ability to regulate the alternative splicing of apoptotic gene transcripts.…”
Section: Discussionsupporting
confidence: 76%
“…To identify small molecules that regulate alternative splicing, 1,040 FDA-approved drugs and compounds were screened using RT-PCR in C33A cells, a cervical cancer line. As described in our previous study, Emetine regulated alternative splicing of the Bcl-x gene (15). Notably, Emetine was also found to increase the smaller caspase 9b mRNA with a concomitant increase of the larger caspase 9 mRNA (Fig.…”
Section: Resultssupporting
confidence: 79%
“…We previously described that Emetine regulated alternative splicing of Bcl-x, increasing the smaller pro-apoptotic Bcl-xS isoform and decreasing the larger anti-apoptotic Bcl-xL isoform, resulting in the possible sensitization of tumor cells to chemotherapy (15). We further demonstrated that Emetine modulated Bcl-x splicing by affecting PP1 phosphatase.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Six compounds were found to inhibit luciferase expression by ÏŸ75% and reduce cell viability by Ïœ25% (Table 2). Cephaeline and emetine are closely related alkaloid components of ipecac (19) (a wellknown substance used to induce vomiting), and emetine has been shown to inhibit protein synthesis and promote apoptosis in mammalian cells (3,9,13). Emetine appears to be an especially potent inhibitor of translation of viral mRNA in some systems (16).…”
Section: Fig 2 Establishment Of Ebolavirus Minireplicon Assays For mentioning
confidence: 99%